Case-Based Reasoning in Scheduling: Reusing Solution Components - Cunningham, Padraig; Smyth, Barry (Trinity College Dublin, Department of Computer Science, 1996)
In this paper we explore the reuse of components of known good schedules in new scheduling problems. This involves accumulating a case-base of good quality schedules, retrieving a case (or cases) similar to a new scheduling problem and building a new schedule from components of the retrieved cases. We start by introducing the components of Case-Based Reasoning (CBR) and we describe a CBR solution to a Travelling Salesman Problem in order to illustrate the use of CBR in optimisation problems. Two CBR solutions to a single machine scheduling problem with sequence dependent setup times are described. These are evaluated by comparing them with two more conventional alternative techniques ? simulated annealing and myopic search. Both CBR techniques are shown to provide good quality solutions quickly.
Keywords: Computer Science